KONSTRUKSI YAHUDI DI BARAT DAN TIMUR: ANALISIS MULTIMODAL HALLIDAY PADA NOVEL GRAFIS - Nursani, Asyipa; Firmonasari, Aprillia (Adabiyyāt: Jurnal Bahasa dan Sastra, 2024)
This research aims to analyze how Jewish identity is constructed in the West and the East, as represented in the graphic novels Fagin the Jew by Will Eisner and The Last Jew in Penang by Zayn Gregory and Arif Rafhan , using Halliday's multimodal approach. This approach focuses on various modes of communication, such as verbal, visual, gestural, and spatial, in constructing the narrative of Jewish identity in both novels. Fagin the Jew portrays Jewish identity in the Western context, specifically in 19th-century London, emphasizing antisemitic stereotypes and social marginalization. In contrast, The Last Jew in Penang depicts Jewish identity in the multicultural environment of Southeast Asia, where Jewish identity is more accepted and assimilated into the local community. The findings reveal that cultural differences significantly influence the representation of Jewish identity in these two novels. Through an analysis of verbal, visual, gestural, and spatial modes, it is found that Western graphic novels tend to depict Jewish identity in narratives of prejudice and alienation, while Eastern graphic novels highlight narratives of coexistence and adaptation. This research concludes that multimodality plays a crucial role in reflecting the complexity of Jewish identity shaped by differing historical, social, and cultural contexts in the West and the East.